Polymorphisms in SREBF1 and SREBF2, two antipsychotic-activated transcription factors controlling cellular lipogenesis, are associated with schizophrenia in German and Scandinavian samples - Hellard, Stephanie Le; Mühleisen, T. W.; Djurovic, S.; Fernø, J.; Ouriaghi, Z.; Mattheisen, M.; Vasilescu, C.; Raeder, M. B.; Hansen, T.; Strohmaier, Jana; Georgi, A.; Brockschmidt, F. F.; et al. (Molecular psychiatry, 2010)
Several studies have reported structural brain abnormalities, decreased myelination and oligodendrocyte dysfunction in schizophrenia. In the central nervous system, glia-derived de novo synthesized cholesterol is essential for both myelination and synaptogenesis. Previously, we demonstrated in glial cell lines that antipsychotic drugs induce the expression of genes involved in cholesterol and fatty acids biosynthesis through activation of the sterol regulatory element binding protein (SREBP) transcription factors, encoded by the sterol regulatory element binding transcription factor 1 (SREBF1) and sterol regulatory element binding transcription factor 2 (SREBF2) genes. Considering the importance of these factors in the lipid biosynthesis and their possible involvement in antipsychotic drug effects, we hypothesized that genetic variants of SREBF1 and/or SREBF2 could affect schizophrenia susceptibility. We therefore conducted a HapMap-based association study in a large German sample, and identified association between schizophrenia and five markers in SREBF1 and five markers in SREBF2. Follow-up studies in two independent samples of Danish and Norwegian origin (part of the Scandinavian collaboration of psychiatric etiology study, SCOPE) replicated the association for the five SREBF1 markers and for two markers in SREBF2. A combined analysis of all samples resulted in highly significant genotypic P-values of 9 × 10−4 for SREBF1 (rs11868035, odd ration (OR)=1.26, 95% confidence interval (CI) (1.09-1.45)) and 4 × 10−5 for SREBF2 (rs1057217, OR=1.39, 95% CI (1.19-1.63)). This finding strengthens the hypothesis that SREBP-controlled cholesterol biosynthesis is involved in the etiology of schizophrenia.
Online veröffentlicht 21 Oktober 2008
Gesehen am 10.03.2023